Child poverty in argentina and the existential minimum (Revista Direitos Humanos e Democracia, 2025)
Currently, 65.5% of children in Argentina are poor according to UCA (Universidad Católica Argentina) measurements. The aim of this article is to consider the serious situation of child poverty in Argentina, and to analyze the discussion on the Existential Minimum. The method followed is that of the illustrious Brazilian jurist Pontes de Miranda. The methodologies are the review of doctrine, national and international documents. First, the institute of the Existential Minimum is considered in the doctrine. Secondly, observations are made on childhood poverty in Argentina. Finally, the need for the institutionalization of the Existential Minimum for Children in Argentina is concluded. After the analysis of the situation of poverty in childhood as well as the doctrinal discussion on the existential minimum, it can be concluded that one way to combat child poverty in Argentina is the institutionalization of the “Existential Minimum” for childhood in this country.
Keywords: Childhood; poverty; minimal existence